How do people with physical disabilities want to construct virtual identities with avatars? - Park, Jaeyoung; Kim, Seongcheol (Frontiers in Psychology, 2022)
In the virtual world, people can reconstruct their identity the way they want with avatars. Many expect the high degree of freedom in avatar customization will give new chances to socially marginalized people experiencing discrimination against their physical traits. Accordingly, research on a virtual embodiment of marginalized people has been steady with increased interest in equity and inclusion. However, even discourse alienates people with disabilities. In addition, there are few studies on the virtual representations of people with disabilities. Therefore, this paper explores the shared perception of avatar-based disability representations among people with disability to help understand how they want to construct their disability with avatars. The study also gives direction for a barrier-free virtual world. We conducted semi-structured in-depth interviews with people with physical impairments who used virtual world services and performed a core-periphery analysis of social representations. This study expands the range of academic adoption of the social representations theory and provides insights for stakeholders such as service providers to design an inclusive virtual world.